Predicting the psychological resilience levels of university students according to some variables - Goksel-Oflas, Suna; Yuksel-Sahin, Fulya (PEGEM AKAD YAYINCILIK EGITIM DANISMANLIK HIZMETLERI TIC LTD STI, 2019)
The study examines whether university students' psychological resilience levels are predicted by gender roles, intercultural sensitivity, risk factors, and sex. It also investigates whether there is any significant difference between the psychological resilience levels of university students studying in different faculties (Education, Engineering, and Art & Design). The study sample consists of 519 university students (313 female, 206 male). The Psychological Resilience Scale, Gender Roles Attitude Scale, Intercultural Sensitivity Scale, a List for Identifying Risk Factors and a Personal Information Form were employed to obtain the study data. Linear Regression analysis and Variance Analysis technique was performed. The results of the study revealed that as variables, gender roles, intercultural sensitivity, and having the risk factors are significant predictors of the psychological resilience levels of the university students. However, gender was not found to be a significant predictor of the students' psychological resilience levels. Similarly, there was no significant difference between the psychological resilience levels of students attending different faculties.
Keywords: Psychological resilience; Gender roles; Intercultural sensitivity; Risk factors; PROTECTIVE FACTORS; SEX-ROLES; GENDER; EXPERIENCE; Education & Educational Research